2002
DOI: 10.1046/j.0022-3042.2001.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Participation of protease‐activated receptor‐1 in thrombin‐induced microglial activation

Abstract: Activation of microglia, the resident macrophages in the CNS, plays a significant role in neuronal death or degeneration in a broad spectrum of CNS disorders. Recent studies indicate that nanomolar concentrations of the serine protease, thrombin, can activate microglia in culture. However, in contrast to other neural cells responsive to thrombin, the participation of novel protease-activated receptors (PARs), such as the prototypic thrombin receptor PAR1, in thrombin-induced microglial activation was cast in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
174
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(191 citation statements)
references
References 77 publications
(139 reference statements)
16
174
1
Order By: Relevance
“…In the case of pb-thr, there is strong evidence for the combination (Hanisch et al, 2004;Weinstein et al, 2005). Microglia are known to express PARs (Balcaitis et al, 2003;Suo et al, 2002Suo et al, ,2003 and as seen here (see Fig. 1) and previously (Weinstein et al, 2005), pharmaceutical-grade rh-thr induces small increases in CD95(Fas) and CD40 expression in the N9 cell line.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In the case of pb-thr, there is strong evidence for the combination (Hanisch et al, 2004;Weinstein et al, 2005). Microglia are known to express PARs (Balcaitis et al, 2003;Suo et al, 2002Suo et al, ,2003 and as seen here (see Fig. 1) and previously (Weinstein et al, 2005), pharmaceutical-grade rh-thr induces small increases in CD95(Fas) and CD40 expression in the N9 cell line.…”
Section: Discussionsupporting
confidence: 66%
“…Dosages were selected to be within the range used in previously reported results (Badie et al, 2000;Hooper et al, 2005;Jarvis et al, 1999;Ryu et al, 2000;Suo et al, 2002;Weinstein et al, 2005). CD95 (Fas) a member of the TNF receptor family is a key microglial surface antigen and is upregulated in a variety of neuroinflammatory conditions (Choi and Benveniste, 2004;Lee et al, 2000).…”
Section: Effect Of Pmx On Factor-induced Surface Antigen Regulation Imentioning
confidence: 99%
“…Notably, in adult animals, PAR1 is expressed at moderate to high levels in brain regions involved with emotional learning, including hippocampus and amygdala (Striggow et al, 2001). PAR1 has been extensively studied for its role in coagulation and hemostasis (Coughlin, 2000;Macfarlane et al, 2001), as well as in the survival of neurons following ischemic, traumatic, or neurotoxic insults (Gingrich & Traynelis, 2000a;Shibata et al, 2001;Riewald et al, 2002;Suo et al, 2002;Cheng et al, 2003;Junge et al, 2003;Xi et al, 2003;Guo et al, 2004;Olson et al, 2004;Hamill et al, 2005;Nicole et al, 2005). Surprisingly little, however, is known about PAR1's roles in normal brain function.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombin-mediated microglial activation has been reported (Moller et al, 2000;Suo et al, 2002). Thrombin is generated from the precursor prothrombin that is endogenously expressed in human, mouse, and rat brain, including dopaminergic neurons in the SN (Dihanich et al, 1991;Soifer et al, 1994;Weinstein et al, 1995).…”
Section: Molecules Involved In Microglial Activation and Signal Transmentioning
confidence: 99%
“…Thrombin is generated from the precursor prothrombin that is endogenously expressed in human, mouse, and rat brain, including dopaminergic neurons in the SN (Dihanich et al, 1991;Soifer et al, 1994;Weinstein et al, 1995). Thrombin-induced microglial activation involves protease-activated receptor-1 (PAR-1) (Suo et al, 2002). Recent studies demonstrated that direct injection of thrombin into various brain parenchyma including hippocampus and substantia nigra results in induction of iNOS, COX-2 and NADPH oxidase-mediated superoxide generation from microglial and subsequent neuronal degeneration (Choi et al, 2003;.…”
Section: Molecules Involved In Microglial Activation and Signal Transmentioning
confidence: 99%